Heat transfer analysis of compound multi-layer insulation for cryogenic tank under different service conditions. Issue 1 (May 2016) - Zhu, H L; Yao, C; Li, Y; Pan, H L
Abstract: Future space missions require efficient delivery of large payloads over great distances, necessitating the use of high-energy cryogenic propellant. Therefore, reliable compound multi-layer insulation on cryogenic tank is a crucial part of future space exploration. Compound multi-layer insulation is composed of double-aluminized radiation shielding and separated by a combination of netting and bumper strips, with a foam substrate. Considering conduction, convection, and radiation in heat transfer, the thermal field of multi-layer insulation is analysis by theoretical analysis with different thickness of foam substrate and MLI. Based on the formerly theoretical analysis, the heat flux and apparent thermal conductivity are discussed under the different thickness of foam substrate and MLI. Finally, the optimum design of multi-layer thermal insulation is present in consideration of the thickness and insulation performance of multi-layer insulation.